2013
DOI: 10.3402/ejpt.v4i0.21382
|View full text |Cite
|
Sign up to set email alerts
|

PTSD and re-offending risk: the mediating role of worry and a negative perception of other people's support

Abstract: BackgroundStudies of posttraumatic stress disorder (PTSD) are mainly focused on victims of trauma. Very few studies explored the links between PTSD symptoms and re-offending risk in perpetrators of violence.Objective The aim of the study was to assess the effect of PTSD symptoms on re-offending risk in prisoner populations with a focus on indirect effects of worry and a negative perception of other people’s support on the relationship between PTSD and re-offending risk.Methods75 prisoners (25 females, mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 94 publications
(96 reference statements)
2
21
0
Order By: Relevance
“…Evident among many participants were similar reactions to the isolation and loss of freedoms prompting flight rather than fight responses early on. Similar to previous research ( Ardino, Milani, & Di Blasio, 2013 ; Evans, Ehlers, Mezey, & Clark, 2007 ; Wakeling & Barnett, 2011 ), men with their first incarceration were particularly vulnerable to negative ruminating thoughts from which there was little opportunity for respite. Work in masculinities and suicidality ( Oliffe et al, 2017 ) also suggests that social isolation is a significant risk factor for self-harm, and perhaps the prospect of being isolated in the long term heightened participant’s vulnerability.…”
Section: Resultssupporting
confidence: 79%
“…Evident among many participants were similar reactions to the isolation and loss of freedoms prompting flight rather than fight responses early on. Similar to previous research ( Ardino, Milani, & Di Blasio, 2013 ; Evans, Ehlers, Mezey, & Clark, 2007 ; Wakeling & Barnett, 2011 ), men with their first incarceration were particularly vulnerable to negative ruminating thoughts from which there was little opportunity for respite. Work in masculinities and suicidality ( Oliffe et al, 2017 ) also suggests that social isolation is a significant risk factor for self-harm, and perhaps the prospect of being isolated in the long term heightened participant’s vulnerability.…”
Section: Resultssupporting
confidence: 79%
“…PTSD may be associated with a risk for repeat victimization, within and outside of the prison system ( 68 ). Moreover, exposure to violence and PTSD has been associated with violent behavior during imprisonment and elevated risks of reoffending afterward ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that posttraumatic cognitive-affective appraisals such as guilt, self-blame and a general negative view of the self are etiologically important in the development of PTSD after the perpetration of an offense (Crisford et al, 2008;Evans, Ehlers, Mezey, & Clark, 2007). In line with this, there is evidence of a pathway from PTSD, via cognitive factors such as worrying and rumination, to violence and the risk of re-offending (Ardino et al, 2013).…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, a clinically reliable improvement was reached on these appraisals (>50%; Ogles, 2013). This is important because cognitive factors might mediate the pathway between PTSD and re-offending (Ardino et al, 2013). Controlled studies are of course still needed to investigate the specific role of cognitions in PTSD after offending.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation